Use of naloxone for reversal of life-threatening opioid toxicity in cancer-related pain. (February 2016) - Howlett, Christina; Gonzalez, Rosa; Yerram, Prakirthi; Faley, Brian
Objective: To review the emergency-based approach to opioid toxicity reversal in cancer-related pain patients. Data source: A MEDLINE and PubMed search was conducted (1966 to May 2014) using the terms opioids, cancer, naloxone, respiratory depression, morphine, morphine derivatives, emergency, and anaphylaxis. Methods of study selection: English articles in human subjects identified from the MEDLINE and PubMed search were evaluated. Citations were excluded if they addressed acute overdoses, non-cancer pain, and/or acute, non-chronic pain. Data extraction and synthesis: Pain is a common occurrence in the oncology population. Although toxicity from opioids is common, life-threatening toxicities are not. The use of naloxone in this particular patient population occurs frequently for any perceived opioid-related effect and can be detrimental to the oncology patient's care and quality of life. Difficulties exist when attempting to separate opioid toxicity from disease progression or metastases and, therefore, a thorough history is needed prior to complete opioid reversal in this population. Severity of the opioid intoxication should dictate reversal strategy. Dosing strategies that take into account both the treatment of the opioid-related effects as well as the negative effects reversal will have on the patient are offered. We also review the pre-hospital setting and identified the need for protocols that not only take the patient's symptoms into account, but also the patient's cancer history. Conclusion: Opioid reversal protocols should be developed by a multi-disciplinary team. Each protocol should differentiate those toxicities which are life-threatening and require complete opioid reversal with toxicities that require small aliquots of naloxone to mitigate the presenting symptoms.